Kyai Husein Muhammad’s Perspective on Gender Equality in Efforts to Reconstruct Indonesian Women’s Role in the 20th Century - Jamil, Rahmah Raini; Usuluddin, Win (Advances in Humanities and Contemporary Studies, 2024)
The discourse on women is synonymous with discussions of oppression, violence, discrimination, subordination, and the patriarchal domination over women’s existence. Women seem to lack the space and time to voice their rights like men. Over time, the discourse on gender equality has been advocated by several figures who are aware of the injustices women have experienced. The fate of women in various countries is almost similar, and the women in Indonesia at the beginning of the 20th century also experienced similar challenges. The women’s movement began to emerge, although it was not yet widespread. Towards the end of the 20th century, a prominent Indonesian Muslim feminist figure, Kyai Husein Muhammad, emerged, striving to defend women’s legitimate rights in the public sphere.This research adopts a qualitative descriptive historical approach, using historical research methodology including heuristics, verification, interpretation, and historiography. Based on the findings of this research, it can be concluded that the general contestation of women’s role in Indonesia at the beginning of the 20th century revealed that many women did not receive their rights on par with men. The women’s movement existed but was still limited. In the mid-20th century, the women’s movement grew, though not yet comprehensive. Towards the end of the 20th century, Indonesian women made significant progress and succeeded in obtaining public space to voice their rights. Kyai Husein became a phenomenal figure thanks to his contributions in advocating for women’s rights, earning him the title of a feminist Kyai. He held the perspective that men and women are equally human. Women are the mothers of humanity, entitled to possess all their human potential in capacities relatively equal to men.